2017
DOI: 10.1038/nature23910
|View full text |Cite
|
Sign up to set email alerts
|

Maternal gut bacteria promote neurodevelopmental abnormalities in mouse offspring

Abstract: Maternal immune activation (MIA) contributes to behavioral abnormalities associated with neurodevelopmental disorders in both primate and rodent offspring1-4. In humans, epidemiological studies suggest that exposure of fetuses to maternal inflammation increases the likelihood of developing Autism Spectrum Disorder (ASD)5-7. We recently demonstrated that interleukin-17a (IL-17a) produced by Th17 cells, CD4+ T helper effector cells involved in multiple inflammatory conditions, is required in pregnant mice to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
489
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 540 publications
(512 citation statements)
references
References 29 publications
20
489
1
2
Order By: Relevance
“…The GI flora has been shown to be altered in many disease states, such as cardiovascular disease, 17 24 neurodevelopmental abnormalities in murine offspring, 25,26 and asthma. 27 In the current study, we therefore specifically investigated if the GI flora may also be of importance for the pathogenic responses in antibody-mediated TRALI.…”
Section: Discussionmentioning
confidence: 99%
“…The GI flora has been shown to be altered in many disease states, such as cardiovascular disease, 17 24 neurodevelopmental abnormalities in murine offspring, 25,26 and asthma. 27 In the current study, we therefore specifically investigated if the GI flora may also be of importance for the pathogenic responses in antibody-mediated TRALI.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the infectious agents themselves most often do not enter the fetal circulation, and experiments demonstrating that specific cytokine antagonists in the presence of infection protect the fetal brain from adverse outcomes have implicated the critical role of the maternal immune response itself [26]. A more recent series of studies using this model pinpoints the role of maternal Th17 cell-derived IL-17a as critical in producing a striking cortical patching phenotype in offspring, alongside autism-like behavioral abnormalities [3436]. In contrast to these pre-clinical data, a recent study in humans links high levels of maternal IL-17a during the first trimester to better cognitive outcomes in children by 4 years of age, rather than the opposite [37].…”
Section: Environmental Factors Affecting Microglial Developmentmentioning
confidence: 99%
“…This protection was associated with alterations to the gut microbiome of the offspring, resulting in a more “anti-inflammatory” environment. Similarly, the impact of MIA with poly I:C on maternal IL-17a and fetal outcomes was recently demonstrated to depend on the precise microbiota present in the maternal gut [34,35]. In sum, these data point toward an inter-relatedness of various components of the developing nervous and immune systems, environment, and microglial function, and suggest potential mechanisms by which a greater understanding of environmental impacts on glial development and biology might lead to therapeutic benefits in the treatment and prevention of neurological disorders.…”
Section: Building Better Models and Conclusionmentioning
confidence: 99%
“…Interestingly, modeling MIA-induced ASD offspring in mice resulted not only in behavioral disturbance but also alterations in gut microbiota, which were however reversed by treatment with Bacteroides fragilis ( B. fragilis ) 62). More recent findings have suggested that the microbiome plays a crucial role in modulating environmental and genetic risk factors for development of ASD 63,64). The relationship between microbiota and microglial activation has lately been further studied.…”
Section: Immunomodulatory Treatmentmentioning
confidence: 99%